Nucleotide sequence and characterization of the cryptic Bacillus thuringiensis plasmid pGI3 reveal a new family of rolling circle replicons. - Hoflack, L (1997)
The complete nucleotide sequence of plasmid pGI3 from Bacillus thuringiensis subsp. thuringiensis H1.1. was obtained. Although this 11,365-bp molecule contained at least 11 putative open reading frames (ORFs), extensive database searches did not reveal any homologous sequences with the exception of ORF6, which displayed similarity to the largest ORF of pSTK1, a 1,883-bp cryptic plasmid isolated from Bacillus stearothermophilus. Deletion analysis to determine the pGI3 minimal replicon revealed that ORF6 is the rep gene. Replication occurred via a single-stranded DNA (ssDNA) intermediate, as demonstrated by S1 treatment and Southern hybridization in nondenaturating conditions. Interestingly, however, no homology was found between the pGI3 (ORF6) and pSTK1 (ORF3) rep genes and those from other single-stranded DNA plasmids, nor was there any DNA similarity to the double-strand origins of replication characterized so far, indicating that pGI3 and pSTK1 form another, new family of ssDNA plasmids. PCR analysis revealed that the pGI3 rep gene is largely distributed among B. thuringiensis strains but can also be found in B. cereus and B. mycoides strains, albeit at a lower frequency. Finally, segregation experiments performed with B. subtilis and B. thuringiensis showed that the pGI3 derivatives, including the minimal replicon, were segregationally stable at temperatures suitable for B. thuringiensis growth (<43 degrees C).